EFEKTIFITAS MEDIA KARTU BERJENDELA DALAM MENINGKATKAN KEMAMPUAN DALAM MENGENAL KONSEP WARNA PRIMER BAGI ANAK TUNAGRAHITA SEDANG - Teza Priska Arsi (Jurnal Penelitian Pendidikan Khusus, 2012)
Abstract: This research background by Tunagrahita Medium Children who are not familiar with the concept of the primary colors (red, yellow and blue). Based on the case study aims to demonstrate the effectiveness of the media card in introducing the concept of a windowed primary colors.This research uses the methods of experimental research Single Subject Reasearch (SRR) with the design of the A1-A2-B. Subjects were children tunagahita're X class 1/C1. Assessment in this study are consistent and measure children's ability to match, shows and mentions the primary colors and the assessment presented in the form of a percentage. The results of this study indicate that the ability of children being x mental retardation in the concept of primary colors increases, the initial baseline condition (A1) is done as much as ten times the observation of the child knows only one concept of primary colors of red, the intervention condition twelve observation time increases with the child's ability to use the media card windowed approach is able to match children, shows and mention all the primary colors. And the last is kegiantan baseline (A2), this activity was performed seven times of observation, after intervention was stopped, ternyatan child's ability to maintain its ability to match, show and said primary colors. Thus proved the hypothesis put forward that the media card is windowless effective in improving primary color concept of mental retardation in children being x kelas1/C1 in SDLB N 36 Muaro District Sijunjung Sijunjung district. In connection with the study results in the concept of mental retardation in children of primary colors being x increases, the researchers suggest the teacher to use the media card is windowed in improving the concept of primary colors for future learning.